Z. Varga, G. Ronkay, P. Gyulai, A. Kiss & L. Ronkay A Taxonomic Atlas of the Eurasian and North African Noctuoidea. Noctuinae III. Poliina - Vives Moreno, A. (SHILAP Revista de lepidopterología, 2020)
Book Reviews